Mortgage regulation and financial vulnerability at the household level - Knut Are Aastveit; Ragnar Enger Juelsrud; Ella Getz Wold (Norges Bank, 2020)
We evaluate the impact of mortgage regulation on credit volumes, household balance sheets and the reaction to adverse economic shocks. Using a comprehensive dataset of all housing transactions in Norway matched with buyers' balance sheet information from official tax records, we identify causal effects of mortgage loan-to-value (LTV) limits. Our results show that LTVrequirements have substantial effects on credit volumes, especially on the extensive margin. As a result, such requirements contribute to dampening aggregate credit growth. We find that affected households lower their debt uptake and face lower interest expenses, thereby reducing their vulnerability to adverse shocks. However, affected households also deplete liquid assets when purchasing a home, in order to meet the new requirement. This negative effect on liquid savings persists in the years following the house purchase, suggesting that the impact on financial vulnerability at the household level is in fact ambiguous. We illustrate this further by documenting that households affected by the regulation are more likely to sell their home when becoming unemployed compared to non-affected households.
hdl:11250/2672678
Keywords: E21; E58; G21; G28; G51; 330; Household leverage; Financial regulation; Macroprudential policy; Mortgage markets